Potential Utilization of Plant Growth Promoting Rhizobacteria (PGPR) and Various Growing Media on Soil Fertility in Dry Land - Demy Afiya Restiyah; Taufik Fauzi; Suwardji; A. A. Ketut Sudharmawan (Jurnal Biologi Tropis, 2023)
The potential of dry land for agricultural development in Indonesia is very large, one way that can be done to increase soil fertility and productivity of dry land is by using PGPR biologival fertilizers and various planting media such as husk charcoal and cocopeat. The purpose of this writing is to determine the effect of giving Plant Growth Promoting Rhizobacteria and various planting media on soil fertility in dry land. This research was conducted using a descriptive method by obtaining data from publication in the form of research journal, review journal published in international and national journals and other related information. Descriptive analysis was carried out by means of 1). Do a search of appropriate literature 2). Screening and selecting relevant articles 3). Conducting qualitative analysis and 4). Compile articles. The application of PGPR and various planting media can increase the physical and chemical fertility of the soil and nutrient absorption for the soil, such as improving soil ph, organic C, P-total and soil N-total. The mechanism of PGPR to increase soil fertility is by fixing nitrogen in the air with the help of the enzyme nitogenase, as a phosphate solvent, and as a producer of plant hormones.